The American factor influence on the British position during the Iranian oil crisis 1951-1953 (Raparin Journal of Humanities (RJH), 2024)
The issue of nationalizing oil in Iran has already been addressed by researchers in previous studies that were characterized by comprehensiveness، However، this study attempts to shed light on the ongoing controversy in some aspects related to the British position، which were not resolved in previous studies، in light of the data which we obtained from unpublished documents and the recently published British and American documents and memoirs of decision makers in the countries concerned. There are still those who believe that the oil interests of Western companies were the most important factor in formulating the British and American decision، but there is another school that believes that the security factor and the exigencies of the Cold War were the most important factor in resolving matter the way it was done. This study is an attempt to shed further light on this controversy.The study will give special importance to the American factor and its influence on the British position during the Iranian oil crisis. The importance of the research is evident in the fact that it specializes in studying the first real attempt by a country that seeks to nationalize one of its most important resources in the Middle East in the atmosphere of the Cold War. Therefore، the study is an attempt to explain and analyze how and why the government of Muhammad Mosaddeq was seeking to nationalize Iranian oil ، and we discuss the challenges it faced in order to achieve that goal.As for the methodology of the paper، we study the debate on the subject by following the historical methodology in addressing the issues in a chronological way and critically analyzing the discourse. While doing the analyses، we compare the British archival material with that of American and the Iranian. The collected data from the archival material will be used to evaluate the previous studies in the field. As for the structure of the research، it consists of an introduction، two sections، and the conclusion. In the preface، light is shed on a historical renunciation of the Anglo-Iranian company. As for the first section، it is devoted to studying the development of British oil interests in Iran (1902-1951)، in which the conflicting British and Russian interests towards Iranian oil addressed. Besides، the differences between the views of the Iranian government and the Anglo-Iranian Oil Company during 1947-1951 on the oil crisis are explained in detail. The second topic deals with the stand of the United States of America on the oil crises and its impact on formulating British position during the Iranian oil crisis 1951-1953.While explaining the US stand on the crisis ، we will point the two distinct stages in this regard .Finally ، we explain and discuss how the US and British government had eventually reached the conclusion that a joint efforts were needed to overthrow the government of Muhammad Mossadegh on August 19، 1953. In the end study will present its most important findings.